Incremental Forming as a Rapid Tooling Process - Afonso, Daniel; Alves de Sousa, Ricardo; Torcato, Ricardo; Pires, Liliana (Manufacturing and Surface Engineering, 2019)
This book discusses the general concept and applications of rapid tooling technologies and introduces the use of incremental forming for the development of rapid sheet tools. Methods and techniques for tool design and development are discussed, considering their manufacture using incremental forming and complementary processes. The mechanical and thermal performance of sheet metal tools is analyzed. Finally, possible applications are introduced, with the description of some case study examples. .